2013
DOI: 10.4172/2157-7412.s1-014
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and In vivo Model Systems for Hemophilia A Gene Therapy

Abstract: Hemophilia A is a hereditary disorder caused by various mutations in factor VIII gene resulting in either a severe deficit or total lack of the corresponding activity. Recent success in gene therapy of a related disease, hemophilia B, gives new hope that similar success can be achieved for hemophilia A as well. To develop a gene therapy strategy for the latter, a variety of model systems are needed to evaluate molecular engineering of the factor VIII gene, vector delivery efficacy and safety-related issues. Ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Hemophilia is a relatively common disease among privately owned dogs, with an estimated 60 new cases diagnosed each year in the US through the Comparative Coagulation Laboratory at Cornell University (personal communication, Marjory Brooks, 2015). Although the prevalence of HA in dogs in unknown, most of these cases are HA, as in humans, suggesting that an endogenous mechanism of mutation in the F8 gene is relatively common among mammals, as naturally occurring HA has also been reported in rats [ 25 ], sheep [ 26 ], cats, and horses (review in [ 27 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Hemophilia is a relatively common disease among privately owned dogs, with an estimated 60 new cases diagnosed each year in the US through the Comparative Coagulation Laboratory at Cornell University (personal communication, Marjory Brooks, 2015). Although the prevalence of HA in dogs in unknown, most of these cases are HA, as in humans, suggesting that an endogenous mechanism of mutation in the F8 gene is relatively common among mammals, as naturally occurring HA has also been reported in rats [ 25 ], sheep [ 26 ], cats, and horses (review in [ 27 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Human mesenchymal stem cells (hMSCs) have been recently established as a new tool for delivering secreted proteins because they are easy to isolate, expand, and manipulate with genetic modification [10]. Several studies showed that hMSCs derived from adipose tissue, bone marrow or umbilical cord blood are capable of differentiating into hepatocyte-like cells in specialized in vitro culture conditions [1113].…”
Section: Introductionmentioning
confidence: 99%